2004
DOI: 10.1016/j.surfcoat.2003.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, mechanical properties and cutting performance of superhard (Ti,Si,Al)N nanocomposite films grown by d.c. reactive magnetron sputtering

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…Other groups have also studied the Ti-Si-N system and other ternary, quaternary, or even pentanary systems [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. The high hardness of these nanocomposite coatings has already demonstrated superb properties for tribological applications such as in high speed, dry cutting and drilling [42][43][44] and on aero engine turbine blades against severe erosion [45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other groups have also studied the Ti-Si-N system and other ternary, quaternary, or even pentanary systems [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. The high hardness of these nanocomposite coatings has already demonstrated superb properties for tribological applications such as in high speed, dry cutting and drilling [42][43][44] and on aero engine turbine blades against severe erosion [45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, various PVD processes have also been developed including ion beam assisted deposition [30], magnetron sputtering [16][17][18][19][20][21][22][23][24][25][26][27]29,[31][32][33][34][35][37][38][39][40][41][43][44][45][46][47][48], cathodic arc deposition [28,36,58] and hybrid deposition using both magnetron sputtering and arc evaporation [56,57]. Recent reviews on various deposition technologies can be found in refs.…”
Section: Introductionmentioning
confidence: 99%
“…No detailed investigation of the Al-Si-N system has been carried out so far. To our knowledge, only Ti-Si-Al-N [20][21][22], Ti-Al-V-Si-N [21], Ti-Cr-Al-Si-N [23] nitride thin films with a low (≤10 at.%) Si content have been investigated so far. These systems, however, also do not exhibit the thermal stability and oxidation resistance above 1000°C because a low amount of Si prevents the formation of amorphous Al-Si based materials [24].…”
Section: Introductionmentioning
confidence: 99%
“…The coatings of such structure are able to maintain a low friction coefficient (selflubricating coatings) in numerous working environments, maintaining high hardness and increased resistance (Donnet & Erdemir, 2004;. The main concept in the achievement of high hardness of nanostructure coatings and good mechanical properties and high strength related to it, particularly in case of nanocomposite coatings (Holubar et al, 2000;Rafaja et al, 2007;Carvalho et al, 2004), is the restriction of www.intechopen.com Advances in Diverse Industrial Applications of Nanocomposites 2 the rise and the movement of dislocations. High hardness and strength of the nanocomposite coatings are due to the fact that the movement of dislocations is suppressed at small grains and in the spaces between them, which causes the appearance of incoherent deformations.…”
Section: Introductionmentioning
confidence: 99%
“…Various analyses revealed that the synthesized TiAlSiN coatings exhibited nanostructured composite microstructures consisting of solid-solution (Ti,Al,Si)N crystallites and amorphous Si 3 N 4 . The Si addition caused the grain refinement of (Ti,Al,Si)N crystallites and its uniform distribution with percolation phenomenon of amorphous silicon nitride (Zhang & Ali, 2007;Holubar et al, 2000;Rafaja et al, 2007;Carvalho et al, 2004). One of the general reasons for depositing by PVD techniques is that protective coatings deposited by PVD tend to have higher corrosion resistance than the substrate material.…”
Section: Introductionmentioning
confidence: 99%